Concrete‐Inspired Bionic Bone Glue Repairs Osteoporotic Bone Defects by Gluing and Remodeling Aging Macrophages - Chong Li; Wei Xu; Lei Li; Yonghui Zhou; Gang Yao; Guang Chen; Lei Xu; Ning Yang; Zhanjun Yan; Chen Zhu; Shiyuan Fang; Yusen Qiao; et al. (Advanced Science)
Abstract Osteoporotic fractures are characterized by abnormal inflammation, deterioration of the bone microenvironment, weakened mechanical properties, and difficulties in osteogenic differentiation. The chronic inflammatory state characterized by aging macrophages leads to delayed or non‐healing of the fracture or even the formation of bone defects. The current bottleneck in clinical treatment is to achieve strong fixation of the comminuted bone fragments and effective regulation of the complex microenvironment of aging macrophages. Inspired by cement and gravel in concrete infrastructure, a biomimetic bone glue with poly(lactic‐co‐glycolic acid) microspheres is developed and levodopa/oxidized chitosan hydrogel stabilized on an organic‐inorganic framework of nanohydroxyapatite, named DOPM. DOPM is characterized via morphological and mechanical characterization techniques, in vitro experiments with bone marrow mesenchymal stromal cells, and in vivo experiments with an aged SD rat model exhibiting osteoporotic bone defects. DOPM exhibited excellent adhesion properties, good biocompatibility, and significant osteogenic differentiation. Transcriptomic analysis revealed that DOPM improved the inflammatory microenvironment by inhibiting the NF‐κB signaling pathway and promoting aging macrophage polarization toward M2 macrophages, thus significantly accelerating bone defect repair and regeneration. This biomimetic bone glue, which enhances osteointegration and reestablishes the homeostasis of aging macrophages, has potential applications in the treatment of osteoporotic bone defects.